(untitled) (Research, Society and Development, 2023)
In the midst of martial arts modalities, we have the division of each category by the body weight of the athletes. Aiming to seek a greater advantage of the weight measurement mechanism, athletes tend to drop the weight abruptly so that, on the day of the competition, they are heavier than their opponent, thus bringing a certain advantage. Fast weight loss methods are aggressive and can result in several threats to the athlete’s health. Therefore, this review aimed to evaluate the studies related to the hydration of martial arts competitors, and the possible impacts on the athlete’s health and performance in the sport, the forms of weight loss and dehydration used. It was found that a rapid weight loss bigger than 5% of the total body mass causes a significant damage in performance, biochemical markers and psychological aspects in the athlete, this damage is accentuated when more than one method is used for rapid weight loss.